EVALUASI EFEKTIVITAS PENGENDALIAN INTERN SISTEM INFORMASI AKUNTANSI PENGGAJIAN RSUP. PROF. DR. R. D. KANDOU MANADO - Rompas, Richard Antonio; Pangemanan, Sifrid; Kalalo, Meily (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Accounting information systems is a supportive factor in the compannyâs performance. Company will require SIA in this time because SIA provide financial effectively and efficiently. The purpose of this study is to determine whether the effectiveness of internal control payroll accounting information system RSUP. Prof. Dr. R. D. Kandou Mando has gone well. The author uses descriptive analysis where research start by collecting and sifting through incoming information thoroughly and detail later elaborated in order to obtain a clean picture. The results of the study concluded that the payroll accounting system implemented by RSUP. Prof. Dr. R. D. Kandou Manado already have a good system and effective and meet the elementÂ  of internal control to improve compannyâs performance. But thare are very few weaknesses that auditing section not conducting regular monitoring three months once.Keywords: Accounting information system, payroll, effectiveness of internal control